2012
DOI: 10.1158/0008-5472.can-11-4092
|View full text |Cite
|
Sign up to set email alerts
|

PTEN and NF1 Inactivation in Schwann Cells Produces a Severe Phenotype in the Peripheral Nervous System That Promotes the Development and Malignant Progression of Peripheral Nerve Sheath Tumors

Abstract: The genetic evolution from a benign neurofibroma to a malignant sarcoma in patients with neurofibromatosis type 1 (NF1) syndrome remains unclear. Schwann cells and/or their precursor cells are believed to be the primary pathogenic cell in neurofibromas because they harbor biallelic neurofibromin 1 (NF1) gene mutations. However, the phosphatase and tensin homolog (Pten) and neurofibromatosis 1 (Nf1) genes recently were found to be co-mutated in high-grade peripheral nerve sheath tumors (PNSTs) in mice. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 23 publications
7
76
0
Order By: Relevance
“…For example, PI3K–mTOR signalling is enhanced in Nf1 -mutant astrocytes and MPNSTs 90,91 . PI3K–AKT signalling downstream of Rras2 has a role in the initiation of neurofibromas 92 ; activation of the PI3K pathway through loss of Pten in mice promotes the transformation of Nf1 -driven neurofibromas to MPNSTs 93 . Sustained activation of AKT in MPNST cells requires calcium and calmodulin 94 .…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%
“…For example, PI3K–mTOR signalling is enhanced in Nf1 -mutant astrocytes and MPNSTs 90,91 . PI3K–AKT signalling downstream of Rras2 has a role in the initiation of neurofibromas 92 ; activation of the PI3K pathway through loss of Pten in mice promotes the transformation of Nf1 -driven neurofibromas to MPNSTs 93 . Sustained activation of AKT in MPNST cells requires calcium and calmodulin 94 .…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%
“…Importantly, phosphatase and tensin homolog ( Pten) and neurofibromatosis 1 ( Nf1 ) were amongst the many candidate genes identified in this screen that tended to be co-mutated in the same PNSTs. Pten -regulated pathways have been shown to be major tumor suppressive barriers to PNST progression in Schwann cells in the context of Nf1 loss [26]. Recently, it has also been shown that PTEN and EGFR both play important roles in the initiation of PNSTs [27].…”
Section: Mouse Models Of Cancermentioning
confidence: 99%
“…This modeled the co-occurrence of Pten and Nf1 found in PNSTs derived from SB mutagenesis. The loss of both Nf1 and Pten in Schwann cells lead to the rapid onset of high grade PNSTs [26]. …”
Section: Mouse Models Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of numerous accurate small-animal (genetically engineered mouse; GEM) models of NF1-associated nervous system tumors (table 1), [8][9][10][11][12][13][14][15][16][17][18] the creation of the NF Clinical Trials Consortium, 19 and the establishment of response criteria for NF1 clinical trials, 20 the stage has been set for the discovery and validation of promising therapeutic strategies and their translation to people affected with NF1. However, despite these advances, there are currently no effective therapies, which likely reflects the striking biological and clinical heterogeneity inherent to this condition.…”
mentioning
confidence: 99%